A Posteromedial Portal Allows Access to the Posteromedial Knee, While a Posterolateral Portal Risks Common Fibular Nerve Injury: A Cadaveric Analysis - Kelsi Greenwood, B.Sc., M.Sc; Nkhensani Mogale, B.Med.Sc., B.Sc., M.Sc., Ph.D; Reinette Van Zyl, B.Sc., M.Sc; Natalie Keough, Ph.D; Erik Hohmann, M.B.B.S., F.R.C.S., F.R.C.S. (Tr&Orth) (Elsevier, 2024)
Purpose: To investigate the safety and accessibility of direct posterior medial and lateral portals into the knee. Methods: This study was a controlled laboratory study that comprised a sample of 95 formalin-embalmed cadaveric knees and 9 fresh-frozen knees. Cannulas were inserted into the knees, 16 mm from the vertical plane between the medial epicondyle of the femur and the medial condyle of the tibia, and 8 (females) and 14 mm (males) from the vertical plane connecting the lateral femoral epicondyle and lateral tibial condyle. Landmarks were identified in full extension, and cannula insertion was completed with the formalin-embalmed knees in full extension and the fresh-frozen knees in 90 degrees of flexion. The posterior aspects of the knees were dissected from superficial to deep to assess potential damage caused by the cannula insertion. Results: The incidence of neurovascular damage was 9.6% (n = 10): 0.96% for the medial cannula and 8.7% for the lateral cannula. The medial cannula damaged 1 small saphenous vein (SSV). The lateral cannula damaged 1 SSV, 7 common fibular nerves (CFNs), and both the CFN and lateral cutaneous sural nerve in 1 specimen. All incidences of damage occurred in formalin-embalmed knees. The posterior horns of the menisci were accessible in all specimens. Conclusions: A direct posterior portal into the knee with reference to the medial bony landmarks of the knee proved safe in 99% of the cadaveric sample and allowed access to the posterior horn of the medial meniscus. A direct posterior portal with reference to the lateral bony landmarks demonstrated a higher risk of neurovascular damage in the embalmed sample but no damage in the fresh-frozen sample. Given the severe consequences of common fibular nerve injury, recommending this approach at this stage is not advisable. Clinical Relevance: Direct posterior arthroscopy portals are understudied but may allow safe visualization of the posterior knee compartments and may also assist to manage repair of ramp lesions and posterior meniscus pathology.